Hijack it, change it: how do plant viruses utilize the host secretory pathway for efficient viral replication and spread? - Patarroyo, Camilo; Laliberté, Jean-François; Zheng, Huanquan (Frontiers in Plant Science, 2013)
The secretory pathway of eukaryotic cells has an elaborated set of endomembrane compartments involved in the synthesis, modification, and sorting of proteins and lipids. The secretory pathway in plant cells shares many features with that in other eukaryotic cells but also has distinct characteristics important for fundamental cell and developmental processes and for proper immune responses. Recently, there has been evidence that the remodeling of this pathway, and often the formation of viral-induced organelles, play an important role in viral replication and spread. The modification of the host secretory pathway seems to be a common feature among most single-stranded positive ss(+)RNA and even some DNA viruses. In this review, we will present the recent advances in the understanding of the organization and dynamics of the plant secretory pathway and the molecular regulation of membrane trafficking in the pathway. We will also discuss how different plant viruses may interact with the host secretory pathway for their efficient replication and spread, with a focus on tobacco mosaic virus and turnip mosaic virus.